Advances in Terpenoid Biosynthesis: Chemical Diversity and Emerging Industrial Applications - Patil, Harshal Shivaji; Baviskar, Ashwini Sanjay; Dinore, Jaysing Mahavirsing; Yelwande, Ajeet Appasaheb (Sciences of Phytochemistry, 2025)
Terpenoids are the largest and most chemically diverse class of natural products, essential for plant functions such as growth regulation, defense, and ecological interactions. Their extensive chemical variety and functional versatility have also sparked significant industrial interest across many sectors. This review highlights recent progress in terpenoid biosynthesis, especially focusing on the mevalonate (MVA) and methylerythritol phosphate (MEP) pathways, which are the main routes for isoprenoid precursor production. It explores the enzymatic processes that create complex terpenoid skeletons, including detailed cyclization and rearrangement steps carried out by terpene synthases and modifying enzymes. Advances in metabolic engineering and synthetic biology now allow the reconstruction and improvement of terpenoid pathways in microbial and plant systems, greatly increasing production yields. The use of bioinformatics and systems biology tools has further supported pathway discovery, enzyme analysis, and strain development. Beyond their traditional uses in drugs, nutraceuticals, flavors, and fragrances, terpenoids are also promising for biofuels and renewable materials, emphasizing their industrial value. This review addresses challenges such as pathway complexity, precursor supply, and regulatory control, and suggests strategic directions for future research. Overall, these insights reinforce the importance of terpenoids as key targets for sustainable biotech innovations.